Terapi Bermain Peran Dengan Media Animal Action Figure Meningkatkan Kemampuan Komunikasi Verbal Pada Anak Usia 3-4 Tahun: Role-Playing Therapy Using Animal Action Figure Media Improves Verbal Communication Skills in Children Aged 3–4 Years - Siswoaribowo, Andika; Huda, M. Maftuchul; Syafinanda, Maditiya Nur (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
In the development of children’s communication, language plays a crucial role; however, some children experience difficulties in verbal communication. One approach to improving children’s verbal communication skills is through stimulation activities, such as role-playing therapy using animal action figure media. This study aimed to determine the effect of role-playing therapy with animal action figure media on the verbal communication abilities of children aged 3–4 years at PAUD Strawberry Pare. This study employed a quasi-experimental design with a pretest–posttest control group approach. From a population of 45 children, 22 samples were selected using purposive sampling and divided into two groups: 11 children in the intervention group and 11 children in the control group. The research instrument was an observation sheet measuring verbal communication ability. Data were analyzed using the Wilcoxon test and the Mann–Whitney test. The results showed that before the intervention, the majority of children in the intervention group (54.5%) were categorized as having poor verbal communication skills, while after the intervention, all children (100%) were categorized as having good verbal communication skills. In the control group, the pretest results indicated that most children (54.5%) were in the poor category, and the posttest results showed that the majority (63.6%) remained in the poor category. The Mann–Whitney test revealed a p-value of 0.000 (α ≤ 0.05), indicating a significant effect of role-playing therapy using animal action figure media on children’s verbal communication abilities. Animal action figure media were effective in attracting children’s attention and increasing their focus, thereby supporting the improvement of basic vocabulary and articulation skills. Therefore, it is recommended that teachers and parents apply role-playing therapy using animal action figure media regularly, at least once a week, both at school and at home.